Plant species from coal mine overburden dumping site in Satui, South Kalimantan, Indonesia - Vivi Novianti; D N Choesin; D T Iskandar; D Suprayogo (Journal of Degraded and Mining Lands Management, 2017)
Coal mine overburden (OB) materials were nutrient-poor, loosely adhered particles of shale, stones, boulders, and cobbles, also contained elevated concentration of trace metals. This condition cause OB substrate did not support plants growth. However, there were certain species that able to grow on overburden dumping site. This investigation sought to identify plants species that presence on coal mine overburden. The research was conducted on opencast coal mine OB dumping site in Satui, South Kalimantan. Vegetation sampling was carried out on six different ages of coal mine OB dumps (7, 10, 11, 42, 59 and 64 month) using line transect. Species identification used information from local people, AMDAL report of PT Arutmin Indonesia-Satui mine project, and website. There were 123 plant species, consisted of 79 herbs (Cyperaceae, Poaceae and Asteraceae), 10 lianes, bryophyte, 9 ferns, 10 shrubs, and 14 trees. A number of Poaceae, i.e., Paspalumconjugatum, Paspalumdilatatum, and Echinochloacolona generally present among the stones, boulders, and cobbles. While Cyperaceae such as Fimbristylis miliaceae, Cyperus javanicus, Rhyncospora corymbosa and Scleria sumatrensis most often foundinand around thebasin/pond with its smooth and humid substrate characteristics. Certain species of shrubs and trees present on the 7 month OB dumping site. They wereChromolaena odorata, Clibadium surinamense, Melastoma malabathricum, Trema micrantha, and Solanum torvum (Shrubs), Ochroma pyramidale and Homalanthus populifolius (trees). This plant species could be used for accelerating primary succession purpose on coal mine overburden dumping site. Nevertheless, species selection was needed to avoid planting invasive species.